Reduction of Electricity Costs in Medway NHS by Inducing Pro-Environmental Behaviour Using Persuasive Technology (Future Cities and Environment, 2018)
Hospitals represent a busy environment with the majority of the medical operations relying on electricity, for example lighting and medical equipment. Hence, it is important to conserve it to ensure high quality of services, improve patients’ wellbeing as well as to the reduction of the hospitals’ carbon footprint and the impacts on the environment. The studies carried out in hospitals considered the use of renewable energy or the use of power efficient equipment to tackle the energy problem. The challenge remains open in how to tackle the energy problem in a hospital through behavioural change. This study represents a step into reducing electricity costs of Medway NHS Foundation Trust (MNFT) in the UK. The proposed idea is to use technology to persuade MNFT staff to monitor their behaviour and with the right motive, from selected and appointed energy delegates, sustain a pro-environmental behaviour. This paper describes the methodology and system proposed to reduce electricity costs in MNFT by inducing pro-environmental behaviour with the aid of technology. This involves a smart electricity metering system to collect and communicate energy data to a centralised server that pushes the data onto a dedicated web interface. Furthermore, addressing the psychological factors by appointing energy delegates to monitor the consumption, in selected areas, as well as motivate the staff members. In addition, monitoring human dynamics and analysing it against energy data to identify a relation between occupancy and electricity consumption trends in hospital wards.